A mathematical description for the fungal degradation process of biodegradable plastics - Sang, BI; Hori, K; Unno, H (ELSEVIER SCIENCE BV, 2004)
Fungal degradation of biodegradable plastics such as poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) occurred only on the surface covered with fungal hyphae capable to excrete depolymerase, and the fungal degradation of PHBV film was described mathematically. The surface growth of fungi was derived from the notion of equivalent symmetric tree model and was expressed for the two different growth phases, exponential phase and deceleration phase. PHBV degradation by fungi was expressed in terms of the degradation capability of a fungal hypha and the fraction of fungal biomass contributing to PHBV degradation. The proposed growth and degradation models simulated the experimental data obtained from fungal PHBV degradation in soil well and gave insight into fungal PHBV degradation process. (C) 2003 IMACS. Published by Elsevier B.V. All rights reserved.
Keywords: GROWTH; POLY(3-HYDROXYBUTYRATE-CO-3-HYDROXYVALERATE); KINETICS; MODEL; SOIL